Design and Implementation of Peer-to-Peer Video and Chat Communication - Abdullah Saeed, Muath; Edan, Naktal Moaid (Technium Social Sciences Journal, 2022)
Web Real-Time Communication (WebRTC) technology permits real-time media and data exchange between browsers. A connection is proven via a detection procedure named signalling. However, signalling has no exact definition in WebRTC. This paper aims to design and implement WebRTC chat, video communication, and recording between peers (browser-to-browser) in a real application using Chrome and Firefox based on peer-to-peer topology. Thus, a signalling channel between two peers for chat and video conferencing using the following: Socket.io mechanism, Node.JS platform, and Express.JS has been produced and performed. Including, Vanilla JS, Axios (HTTP JSON) and JavaScript as the main programing language utilized. The results of this work have ensured that a signalling channel has been built and implemented.